Evaluation in vitro of the infection times of engorged females of Rhipicephalus (Boophilus) microplus by the entomopathogenic nematode Steinernema glaseri CCA strain - Carvalho,Leandro Barbiéri de (2010)
Studies have shown that ticks are susceptible to infection by entomopathogenic nematodes. These studies indicate different susceptibilities of ticks to infection by these fungi, depending on the tick species, development phase, entomopathogenic nematodes species and strains and the time the ticks are exposed to them. Usually this period ranges from 24 to 72 hours. The aim of this study was to evaluate the infection times in vitro of engorged Rhipicephalus (Boophilus) microplus females by the entomopathogenic nematodes Steinernema glaseri CCA strain, by analysis of the ticks' biological parameters. The results show that a 2-hour exposure time was sufficient for the engorged R. microplus females to be infected by S. glaseri CCA, but that a minimum exposure time of 24 hours was necessary to generate treatment efficacy above 90%.